2011
DOI: 10.1074/jbc.m110.214106
|View full text |Cite
|
Sign up to set email alerts
|

Proton-sensing Ca2+ Binding Domains Regulate the Cardiac Na+/Ca2+ Exchanger

Abstract: This work reveals for the first time that NCX can be switched off by physiologically relevant intracellular acidification and that this depends on the competitive binding of protons to its C 2 regulatory domains CBD1 and CBD2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 47 publications
4
74
0
2
Order By: Relevance
“…For example, ATP depletion causes a significant decrease in cardiac NCX activity (19,20,30,31), and lactate accumulation not only increases cytosolic NADH but also mediates acidosis. Decreased pH inhibits NCX activity (32), which is fully reversible after pH normalization (33). In our study, acidosis is not expected to contribute to the observed lactate-or NADH-mediated I NCX inhibition because cytosolic pH was buffered by dialysis with the pipette solution containing 10 mM HEPES at pH 7.25.…”
Section: Discussionmentioning
confidence: 91%
“…For example, ATP depletion causes a significant decrease in cardiac NCX activity (19,20,30,31), and lactate accumulation not only increases cytosolic NADH but also mediates acidosis. Decreased pH inhibits NCX activity (32), which is fully reversible after pH normalization (33). In our study, acidosis is not expected to contribute to the observed lactate-or NADH-mediated I NCX inhibition because cytosolic pH was buffered by dialysis with the pipette solution containing 10 mM HEPES at pH 7.25.…”
Section: Discussionmentioning
confidence: 91%
“…Equilibrium binding of 45 Ca 2 + to CBD12-1.4 F450G was measured using a protein-ligand ultrafiltration assay [7,12,30]. The F450G mutation results in a notably decreased affinity for Ca 2 + binding at the high-affinity Ca3-Ca4 sites, displaying affinities similar to those observed for isolated CBD1 ( Figure 3E, Table 1) [7,15].…”
Section: The F450g Mutation Uncouples the Two-domain Interactions In mentioning
confidence: 92%
“…Time constants of allosteric NCX1 activation have been measured in the range of 0.1–10 s in membrane patches [10, 1417] and additional studies using caffeine application [1820] or flash-photolysis [21, 22] to generate rapid elevation of [Ca 2+ ] I demonstrated rapid activation of NCX1 by [Ca 2+ ] i . The Ca 2+ half-activation concentration (K mAct ) has been measured in the range of 25–600 nM in both membrane patches and intact cardiomyocytes [17, 18, 2326]. Ottolia et al [27] observed beat-to-beat conformational changes in CBD12 by measuring fluorescent resonance energy transfer in response to changes of [Ca 2+ ] i in cardiomyocytes, but how these changes in CBD12 conformation lead to NCX1 activation remains unclear.…”
Section: Introductionmentioning
confidence: 99%